Bibliometric analysis and research trends on chloride determination in the oil industry - Negris, Luana; Santos, Maria de Fátima Pereira dos; Vicente, Maristela Araújo (Brazilian Journal of Production Engineering, 2023)
The presence of inorganic chlorides, even at low concentrations in petroleum, is associated with a series of operational problems. The determination of inorganic chlorides plays an important role in the petroleum industry. In this study, a bibliometric analysis using the free VOSviewer application and the Web of Science database was performed to provide an overview on the application of chloride determination in petroleum. A total of 3117 articles were analyzed on various aspects of publication characteristics such as publication production, countries, institutions, journals, highly cited articles and keywords. The number of publications in this application has steadily increased over the past 23 years. China and USA were the countries with the highest link strength index. China played a central role in the network of collaboration between the most productive countries. The Federal University of Santa Maria (UFSM) was the institution with the highest link strength (88). Energy & Fuels was the most productive newspaper (173). The keywords surface tension, ionic liquids, emulsion, demulsification, adsorption, zeta potential and wettability are considered critical future research points.
Keywords: Inorganic chlorides; Crude oil; bibliometrics